Evaluation of an Indigenous Traditional Healer and Medicine Program in a Canadian Correctional Facility - Stoliker, Bryce; Jewell, Lisa; Thevenot, Mary-Lou; Ryan, Chaneesa; Nordholt, Nichelle; Mela, Mansfield (The International Indigenous Policy Journal, 2025)
Indigenous Peoples, especially Indigenous women, are overrepresented in Canadian prisons. Given the underlined importance and benefits of culturally-based programs for justice-involved Indigenous people, Canada’s federal correctional system is committed to providing culturally appropriate programs and practices to meet the needs of First Nations, Métis, and Inuit people in custody. Healthcare is one area the federal correctional system is committed to incorporating such programs and practices. This study evaluated the delivery and preliminary outcomes of a culturally-based health program implemented at a women’s healing lodge in Saskatchewan, Canada, which is centred on the provision of traditional medicine and healing practices. A mixed-methods design was used to assess program participants’ (n = 21) and collaborators’ (n = 17) perceptions of the program and its influence on wellness and cultural connectedness. Findings highlight the perceived positive effects on wellness (physical, mental, spiritual health) and cultural connection for women who participated in the program. Discussion considers policy implications, the potential for implementing similar culturally-based health interventions at other (federal) correctional facilities, and the need for further work in this area.